2023
DOI: 10.1111/1759-7714.14996
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stability of pleural fluid carcinoembryonic antigen and its effect on the diagnostic accuracy for malignant pleural effusion

Abstract: Background: The in vitro stability assessment is essential for investigating the diagnostic accuracy of pleural biomarkers. This study aimed to investigate the long-term stability of pleural fluid carcinoembryonic antigen (CEA) at À80 C to À70 C. In addition, we analyzed the effects of frozen storage on the diagnostic accuracy of CEA for malignant pleural effusion (MPE). Methods: Pleural fluid CEA of participants in two prospective cohorts were stored at À80 C to À70 C for 1-3 years. The CEA level in the store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The diagnostic accuracy of CEA for MPE has been published in our previous studies. 29 , 30 In the current investigation, we also compared the diagnostic accuracy of CEA and CA72-4. The AUC of CA72-4 in the combined cohort was lower than that of CEA ( p = 0.006, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic accuracy of CEA for MPE has been published in our previous studies. 29 , 30 In the current investigation, we also compared the diagnostic accuracy of CEA and CA72-4. The AUC of CA72-4 in the combined cohort was lower than that of CEA ( p = 0.006, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies with the same cohort supported this conclusion, which found that the AUC of CEA for MPE was 0.89. 29 , 30 Further studies are needed to investigate whether multiple marker strategies incorporating CA72-4 can improve the diagnostic yield of MPE.…”
Section: Discussionmentioning
confidence: 99%
“…Cytology sensitivity is only between 20% and 60% [ 3 , 8 ]. Previous research discovered that cancer markers such as carbohydrate antigen 125 (CA 125), carbohydrate antigen 15-3 (CA 15-3), carbohydrate antigen 19-9 (CA 19-9), and cytokeratin fragment 21-1 (CYFRA 21-1) have low sensitivity and organ specificity for detecting malignant pleural effusion [ 4 , 9 , 10 ]. As a result, there is an urgent need for a safe, quick, and accurate diagnostic approach for distinguishing between benign and malignant pleural effusions.…”
Section: Introductionmentioning
confidence: 99%